Combination of Polyethylene Terephthalate Nesting and Prone Position at the Standard Box Care to the Vital Signs and Length of Stay on the Low Birth Weight Babies - Meli Deviana; Noor Pramono; Ari Suwondo (GHMJ (Global Health Management Journal), 2020)
Background: The use of nesting and prone position conditioned Low Birth Weight (LBW) babies as the mother's womb that helped in the development of physiological functions and achieve physiological function stability. This study aims to test the effectiveness of designed nesting with polyethylene terephthalate materials and the position of prone with standard care using a box of baby warmers for the length of stay which is observed from the achievement of the stability of vital signs on LBW. Methods: This is a quasi-experimental design study with non-equivalent control group design. The study population was all LBW treated in the Perinatal room with a sample of 36 LBW selected consecutively from newborns at RSUD RAA Soewondo Paô€¦ž and RSUD Dr. R. Soetrasno Rembang. Results: The combination of nesting polyethylene group with position prone achieved faster vital signs stability and shorter duration of treatment compared to the control group with p = 0.001 for temperature, respiration and oxygen saturation. Conclusion: The combination of polyethylene terephthalate nesting and prone position is effective to reduce the duration of treatment and achieving the stability of vital signs of low birth weight infants. This intervention can be used as LBW care during hospital and home care. Keywords: nesting, position prone, polyethylene tread, length of stay, baby vital signs Received: 25 August 2018 Reviewed: 10 September 2018 Revised: 28 June 2020 Accepted: 28 June 2020 DOI: 10.35898/ghmj-41579